The Role of Esophageal pH-metri Test on Gastro-Esophageal Reflux Disease Diagnosis - Katharina Setyawati; Murdani Abdullah; Ari Fahrial Syam; Achmad Fauzi; Dadang Makmun; Marcellus Simadibrata; Chudahman Manan; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2008)
Gastro-esophageal reflux disease is a pathological condition of esophagus which is caused by gastric content reflux into esophagus. There is an increased prevalence of gastro-esophageal reflux disease. The roles of esophageal pH-metry in clinical application include looking for abnormal acid exposure on esophagus with no abnormality found in endoscopy; evaluating patients following the anti-reflux surgery who are being suspected for abnormal esophageal reflux; evaluating patients with normal endoscopic result but still having refractory reflux symptoms against proton pump inhibitor medication; detecting refractory reflux in patients chest pain following the heart evaluation; evaluating patients with otolaryngologic manifestations (laryngitis, pharyngitis, chronic cough) of the esophageal reflux disease after therapeutic failure of 4-weeks proton pump inhibitor treatment; and looking for correlation between adult onset gastro-esophageal reflux disease and non-allergic asthma. Keywords: gastro-esophageal reflux disease, esophagus pH-metry, symptoms-reflux correlation